Activity of STAMP inhibitors in ABL2 rearranged acute lymphoblastic leukemia is dependent on the Abl2 SH3 domain - Elias Lagonik; Elyse C. Page; John B. Bruning; Laura N. Eadie; Susan L. Heatley; Matthew Greenwood; Chun Y. Fong; Andrew S. Moore; David T. Yeung; Timothy P. Hughes; Deborah L. White (Blood Neoplasia)
Abstract: ABL2 rearranged (ABL2r) acute lymphoblastic leukemia (ALL) is a subtype of high-risk Philadelphia chromosome–like ALL. Patients with ABL2r ALL are treated with high-dose multiagent chemotherapy, and the addition of tyrosine kinase inhibitors to their treatment regimen is currently being explored. We have previously demonstrated the in vitro sensitivity of cells harboring the ZC3HAV1::ABL2 fusion to asciminib, the first inhibitor that specifically targets the Abl myristate pocket (STAMP). In this study, we extended these in vitro findings to demonstrate similar sensitivity to the second-generation STAMP inhibitor, TERN-701, using ZC3HAV1::ABL2 ALL cells. In addition, using truncated ZC3HAV1::ABL2 isoforms, we identified that exon 3 of Abl2 (encoded by ABL2) is essential for the efficacy of both STAMP inhibitors. In an in silico model, we further demonstrated that different myristate pocket residues impact the effective binding of asciminib to Abl2 compared to Abl. Importantly, this suggests that, in the clinical setting, different asciminib binding site mutations may be anticipated with STAMP treatment for ABL2r ALL. Finally, we demonstrated the efficacy of both STAMP inhibitors against cells from patients with ZC3HAV1::ABL2 and asciminib as a novel treatment for ZC3HAV1::ABL2 disease in a preclinical in vivo study.